2001
DOI: 10.1080/09500340108231762
|View full text |Cite
|
Sign up to set email alerts
|

Variational analysis of solitary waves in a homogeneous cubic-quintic nonlinear medium

Abstract: Fundamental solitary waves in a cubic-quintic nonlinear medium are investigated both numerically and variationally. An equivalent particle model is used to understand the behaviour of the numerical solutions, and while a super-Gaussian trial function is found to have only a limited range of applicability in the variational analysis, a super-sech trial function is found to match the numerical solutions well for all input powers. Various limits are also investigated.' Present address: Student Support Services,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…The term with ν is large for the case of p-toluene sulfonate crystals. It arises in the nonlinear interaction between Langmuir waves and electrons and describes the nonlinear interaction between the high frequency Langmuir waves and the ion-acoustic waves by pondermotive forces [5][6][7]. There was little attention paid to the propagation of optical beams in the fifth order nonlinear media, since no analytic solutions were known and it seemed that chances of finding any material with significant fifth order term was slim.…”
Section: Parabolic Lawmentioning
confidence: 97%
See 4 more Smart Citations
“…The term with ν is large for the case of p-toluene sulfonate crystals. It arises in the nonlinear interaction between Langmuir waves and electrons and describes the nonlinear interaction between the high frequency Langmuir waves and the ion-acoustic waves by pondermotive forces [5][6][7]. There was little attention paid to the propagation of optical beams in the fifth order nonlinear media, since no analytic solutions were known and it seemed that chances of finding any material with significant fifth order term was slim.…”
Section: Parabolic Lawmentioning
confidence: 97%
“…However, recent developments have rekindled interest in this area. The optical susceptibility of CdS x Se 1−x -doped glasses was experimentally shown to have a considerable χ (5) , the fifth order susceptibility. It was also demonstrated that there exists a significant χ (5) nonlinearity effect in a transparent glass in intense femto-second pulses at 620 nm [5][6][7].…”
Section: Parabolic Lawmentioning
confidence: 99%
See 3 more Smart Citations